Training younger students with intellectual disabilities to pass the standards of the VFSK TRP using a specialized training apparatus - Boyko R.A. ,; Barabash O.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to demonstrate the efficacy of the training apparatus in the context of physical education for elementary school students with mild intellectual disabilities. Methods and structure of the study. The experiment was carried out in the afternoon, during additional physical education classes, at the Amur Region State Educational Institution «Special (Correctional) Secondary School No. 7 in Blagoveshchensk». Two groups were formed, each consisting of 8 participants. The lessons were conducted three times a week for 40 minutes. The study employed methods of pedagogical testing, pedagogical observation, and mathematical statistics. Results and conclusions. The utilization of a drum-like training apparatus empowers individuals with intellectual disabilities to acquire the motor skill of performing pull-ups on both high and low bars with minimal deviations from proper technique. Engaging in exercises on this apparatus fosters strength development, as evidenced by the outcomes of standing and wrist dynamometry at the conclusion of the experiment (p<0,05); and alleviates anxiety and fear when undertaking the strength test of the VFSK TRP for individuals with intellectual disabilities.